Ethnic and Racial Disparities in the Risk of Preterm Birth: A Systematic Review and Meta-Analysis - Schaaf, Jelle M.; Liem, Sophie M.S.; Mol, Ben Willem J.; Abu-Hanna, Ameen; Ravelli, Anita C.J. (American Journal of Perinatology, 2013)
Objectives The aim of this study is to present a systematic review of available literature on the effect of maternal ethnicity (Africans/blacks, Asians, Hispanics, others) on the risk of preterm birth (PTB).Study Design Studies investigating ethnicity (or race) as a risk factor for PTB were included if performing adjustments for confounders. A meta-analysis was performed, and data were synthesized using a random effects model.Results Forty-five studies met the inclusion criteria. Black ethnicity was associated with an increased risk of PTB when compared with whites (range of adjusted odds ratios [ORs] 0.6 to 2.8, pooled OR 2.0; 95% confidence interval [CI] 1.8 to 2.2). For Asian ethnicity, there was no significant association (range of adjusted ORs 0.6 to 2.3). For Hispanic ethnicity, there also was no significant association (range of adjusted ORs 0.7 to 1.5).Conclusions Ethnic disparities in the risk of PTB were clearly pronounced among black women. Future research should focus on preventative strategies for ethnic groups at high risk for PTB. Information on ethnic disparities in risk of PTB-related neonatal morbidity and mortality is lacking and is also a topic of interest for future research.
Keywords: preterm birth; race; ethnicity; systematic review; meta-analysis; perinatal mortality; risk factors